Analisis Hubungan Antara Struktur Suku Bunga, Risiko Kredit, dan Stabilitas Finansial - Maria Yovita R.Pandin; Nesa Mia Kassandra; Lufvi Selvia Febriati; Elfalina Magymai; Tanya Tata Putri Srikandi (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to analyze the relationship between interest rate structure, credit risk, and financial stability in the context of a dynamic financial system. Interest rate is one of the important instruments in monetary policy that affects investment, consumption, and financing decisions in financial markets. The approach applied in this study is a quantitative approach. This method is used to analyze the relationship and impact between research variables in a way that can be measured through numerical data processing and statistical analysis. The analysis shows that there is a significant relationship between interest rates, credit risk, and financial stability, with complex interactions between these factors. Therefore, prudent monetary policy and good credit risk management are necessary to maintain financial stability. This research makes an important contribution to understanding the dynamics of systemic risk in the financial system and can be the basis for developing more effective policies to manage risk and support stable economic growth.